Proton deflectometry of a capacitor coil target along two axes. (2020) - Bradford, P.; Read, M. P.; Ehret, M.; Antonelli, L.; Khan, M.; Booth, N.; Glize, K.; Carroll, D.; Clarke, R. J.; Heathcote, R.; Ryazantsev, S.; Pikuz, S.; et al.
Abstract : A developing application of laser-driven currents is the generation of magnetic fields of picosecond–nanosecond duration with magnitudes exceeding B=10 T . Single-loop and helical coil targets can direct laser-driven discharge currents along wires to generate spatially uniform, quasi-static magnetic fields on the millimetre scale. Here, we present proton deflectometry across two axes of a single-loop coil ranging from 1 to 2 mm in diameter. Comparison with proton tracking simulations shows that measured magnetic fields are the result of kiloampere currents in the coil and electric charges distributed around the coil target. Using this dual-axis platform for proton deflectometry, robust measurements can be made of the evolution of magnetic fields in a capacitor coil target.